The interaction of ice crystals with hailstones in wet growth and its possible role in thunderstorm electrification. (15th April 2016) - Jayaratne, E. R.; Saunders, C. P. R.
Abstract : Charge separation during rebounding collisions of ice crystals on hail particles is a probable mechanism of thunderstorm electrification. Modelling of laboratory results successfully predicts the charge structure in thunderclouds under most conditions. An exception is the intense positive ground flashes observed in mid‐continental severe storms which contain large hailstones that are generally in wet growth. It is difficult to see how interacting ice crystals may separate from the wet surface of a hailstone without sticking, although some studies have reported charge separation during this process. Our laboratory experiments show that, during ice crystal interactions with a simulated hailstone in wet growth, a small but significant charge transfer occurs during ice crystal interactions. We present evidence to show that the hailstone surface is not uniformly wet and consists of dry zones, particularly at the edges, where ice crystals are most likely to impact, and hypothesize that a small number of ice crystals rebounding off these zones may give rise to the observed charging current. While this may explain wet growth charging in laboratory experiments, we cannot directly extend the findings to natural thunderstorms where hailstones tend to rotate and gyrate as they fall, but they may experience different growth regimes within the cloud.